ANALISIS MUTU AIR AKIBAT AKTIVITAS PENAMBANG PASIR DENGAN METODE STORET DI SUNGAI SP PADANG OKI - Yosieguspa Yosieguspa; Ria Fahleny; Yuliani Yuliani (Universitas Sriwijaya, 2021)
Sand mining in the village of Sp Padang is carried out in an open pit mining model through several processes, for example the washing process which is carried out to separate sand from other components.When the sludge in the form of mud and fine sand enters the river, this part causes the quality of river water around the sand mining location to decline. The purpose of this research was to determine the condition of water quality due to sand mining in the river Sp.Padang.The type of data collected is primary data. The research was conducted at 3 stations on the river Sp.Padang.The physico-chemical parameters of river water are used, namely: turbidity, temperature, pH, TSS, DO, BOD, COD, water discharge and current velocity. The data obtained from the laboratory were then analyzed, then comparisons were made with the Storet method.Sampling for water quality replaces the surrounding area with direct measurements and measurements made in the laboratory.The use of the Storet method refers to PP No. 82 of 2001. The principle of Storet is to integrate river water quality data with river water standards and then adjust it according to its use, by classifying water quality into four classes. The results of the data analysis of the quality of river water in Sp.Padang as a result of the sand mining activities are categorized as good class B (lightly polluted) with a score of -6. Sand mining activity affects the water quality of the Sirah River in Padang Island, OKI Regency.Key words : OKI, sand miners, storet method, water quality